Coordination chemistry of silver(I), gold(I) and nickel(II) with bis N-heterocyclic carbenes: applications in electrocatalytic hydrogen evolution reaction. Issue 11 (28th October 2022) - Geetha, B. M.; Yhobu, Zhoveta; Monica, V.; Małecki, Jan Grzegorz; Nagaraju, D. H.; Azam, Mohammad; Al-Resayes, Saud I.; Budagumpi, Srinivasa
Abstract: The design and systematic investigation of an electrocatalyst is crucial in ensuring proper benchmarking of the catalyst developed. This perspective has led to molecular catalysts developed from N -heterocyclic carbene (NHC) metal complexes for electrocatalytic applications. Among the array of electrocatalytic applications available, hydrogen evolution reaction (HER) is at the forefront due to the ever-increasing demand for cleaner and sustainable energy. This work is focussed on the development of binuclear metal-NHC complexes from bis-{4-(2, 6-diethylphenyl)-1, 2, 4-triazole} with a propyl spacer and hexafluorophosphate counterion. The NHC precursor and binuclear silver complexes prepared have been elucidated by single-crystal X-ray diffraction. An assessment of the binuclear complex bearing the same ligand with nickel(II) resulted in the formation of a counter held nickel derivative. The electrocatalytic performance of these metal organic derivatives in HER is evaluated along with their electrochemical impedance spectral discussion. Graphical Abstract: UF0001